Makeup Trends on Television Newcasts in the U.S. during the 20th Century: Exploring High-Definition Television, Journalists, and Appearance - Albarran, Paola Andrea (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2020)
This study is an exploration of the shift from standard definition (SDTV) to high-definition (HDTV) on television newscasts in the United States. This paper examines how this major historic shift affected the thinking, behavior, and trends of female newscasters when using makeup to see what themes arose. Despite the ubiquity of female newscasters, academic research into the influence of HD broadcasting and makeup appearance is limited. Due to this lack of information, the present study provides a cultural approach to examining historical information about this switch. News West 9 broadcasted in Midland-Odessa and interviews to a female newscaster, a news director, and a makeup artist who experienced this shift are utilized to address the historical issues facing high-definition broadcasting during this time.